2013
DOI: 10.3390/md11051553
|View full text |Cite
|
Sign up to set email alerts
|

Spasmolytic Effect of Caulerpine Involves Blockade of Ca2+ Influx on Guinea Pig Ileum

Abstract: In this work, we investigated the spasmolytic effect of caulerpine, a bisindole alkaloid isolated from marine algae of the Caulerpa genus, on guinea pig ileum. Our findings indicated that caulerpine inhibited phasic contractions induced by carbachol (IC50 = 7.0 ± 1.9 × 10−5 M), histamine (IC50 = 1.3 ± 0.3 × 10−4 M) and serotonin (IC50 = 8.0 ± 1.4 × 10−5 M) in a non-selective manner. Furthermore, caulerpine concentration-dependently inhibited serotonin-induced cumulative contractions (pD′2 = 4.48 ± 0.08), shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The whole process of extraction and purification was performed in the Laboratory of Pharmaceutical Technology/UFPB. Figure 1 shows the chemical structure of CLP [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole process of extraction and purification was performed in the Laboratory of Pharmaceutical Technology/UFPB. Figure 1 shows the chemical structure of CLP [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is present in 80% of the species of algae of the genus Caulerpa; however, it can be found in other algae genera [ 19 ]. Diverse biological activities of CLP have been described, including antinociceptive, anti-inflammatory [ 20 ], antiviral [ 21 ], antituberculosis [ 22 ], antineoplastic [ 23 ], and antispasmodic [ 24 ]. Similar to CLP, other bisindole alkaloids have been shown to have anti-inflammatory activity in different parameters of inflammation and have presented different mechanisms of action, ranging from inhibition of the COX-2 pathway to inhibition of the NFκB and MAP kinase pathways and increased expression of adenosine A2A receptors (A2AR) that have anti-inflammatory activity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Albeit an IC 50 for enzyme or receptor inhibition is provided, no mechanism of action studies were reported at the time of publication: alotaketal C ( 224 ) [215]; aspergentisyl A ( 225 ) [216]; A. terreus butyrolactone ( 226 ) [217]; caulerpine ( 227 ) [218]; conicasterol F ( 228 ) [219]; D. avara sesquiterpene ( 229 ) [220]; D. gigantea sterols ( 230 , 231 ) [221]; dysidavarone A ( 232 ) [222]; galvaquinone B ( 233 ) [223]; halicloic acids A and B ( 234 , 235 ) [224]; isochromophilone XI ( 236 ) [225]; leucettamols A and B ( 237 , 238 ) [226]; manadosterol A ( 239 ) [227]; marilines A1 and A2 ( 240 , 241 ) [228]; methyl sarcotroate B ( 242 ) [229]; P. citrinum sorbicillinoid ( 243 ) [230]; phosphoiodyn A ( 244 ) [231]; purpuroines A and D ( 245 , 246 ) [232]; santacruzamate A ( 247 ) [233]; sarcophytonolide N ( 248 ) [234]; sargassumol ( 249 ) [235]; sesquibastadin 1 ( 250 ) [236]; S. glaucum cembranoids ( 251 – 253 ) [237]; symplocin A ( 254 ) [238]; tsitsikammamine A derivative ( 255 ) [239]; V. lanosa bromophenol ( 256 ) [240] ; and X. testudinaria fatty acid ( 257 ) [241]. …”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%
“…CAU shows structural similarity to endogenous indolamines that modulate animal behaviour and a reduction of aggressive behaviour was described in fish exposed to CAU high dose [ 28 ]. Moreover, as already reported in literature, this metabolite exerts a sedative effect via pathways involving serotonin 5-HT3 receptors [ 29 ]. Therefore, the lower difference in metabolic profiles observed for HD and C individuals may be also explained by the onset of anorexigenic effect with the consequent reduction of the amount of CAU ingested.…”
Section: Discussionmentioning
confidence: 63%